Applying the Theory of Planned Behavior: Determinants of Stock Investment Intentions Among Individual Investors in East Java - Dhika Maha Putri; Novi Trisnawati; Sheila Febriani Putri; Selvi Kurniawati (SAINTIS Publishing, 2025)
Psychological and behavioral elements are playing an increasingly prominent role in individual decisions to invest in the stock market. However, understanding how these factors shape investment intentions within specific regional environments remains limited. This study explores the role of attitudes, subjective norms, and perceived behavioral control in influencing stock investment intentions among individual investors in East Java, using the Theory of Planned Behavior (TPB) as its theoretical basis. A total of 353 participants were randomly selected from the Beginner Stock Investor (ISP) community across 13 regions in East Java. Data was collected using an online survey, and the results were analyzed using multiple linear regression. The research findings show that attitude, subjective norms, and behavioral control variables have a positive and significant influence on investment intentions, both independently and collectively. At the individual level, the t-values for attitudes (7.070), subjective norms (3.886), and behavioral control (10.945) all exceeded the threshold of 1.967. The model accounts for 53.3% of the variance in investment intentions, indicating that other relevant factors lie outside the model’s explanatory range. These results reinforce the applicability of TPB in financial behavior studies and offer practical implications for policymakers and investment educators working to improve participation in emerging stock markets.